(untitled) (Training and Practice : Journal of Educational Sciences, 2010)
“An ounce of experience is better than a ton of theory…” (Dewey J., 1922). Cooperative learning is considered a new development in effective learning; it has its roots in the 1920s. Teaching and learning are challenging, because a teacher never knows where his influence stops and when his learners achieve their purpose. Cooperative learning is based on the idea that children can learn in groups with the help of the teacher. In a classroom using cooperative learning, children work on activities in small groups and they receive rewards or recognition based on the overall group performance. Working together, looking at things from a different perspective, being able to really listen to each other, communicating and informing, accepting changes and dealing with these changes in a flexible way, thinking and acting in a creative manner, making use of the possibilities of each individual. These are just some of the skills developed within cooperative learning.